Hypersomatotropism and Hypercortisolism Caused by a Plurihormonal Pituitary Adenoma in a Dog - Elber A. Soler Arias; Ricardo Rodas Elvir; Adrian F. Daly; Hans S. Kooistra (Journal of Veterinary Internal Medicine, 2025)
ABSTRACT A 12‐year‐old, male Labrador Retriever was presented because of polyuria, polydipsia, polyphagia, joint pain, and physical features consistent with acromegaly. Circulating insulin‐like growth factor‐1 (IGF‐1) concentration was increased (> 1000 ng/mL; reference interval [RI], 42–449), suggestive of hypersomatotropism. An abnormal low‐dose dexamethasone suppression test and increased circulating adrenocorticotropic (ACTH) concentration indicated pituitary‐dependent hypercortisolism. Computed tomography identified an enlarged pituitary gland. Treatment with cabergoline initially decreased circulating IGF‐1 and ACTH concentrations and urinary cortisol‐to‐creatinine ratio (UCCR), with a notable reduction in acromegalic physical features. However, 7 months after the start of cabergoline treatment, IGF‐1, ACTH, and UCCR had increased again, although pituitary gland size remained stable. Because of worsening joint pain, euthanasia was performed. On necropsy, double immunohistochemistry identified pituitary tumor cells with cytoplasmic co‐expression of both growth hormone (GH) and ACTH, consistent with a monomorphic plurihormonal macroadenoma. This case shows that concurrent hypersomatotropism and hypercortisolism can occur in dogs caused by a plurihormonal pituitary adenoma.